Bryozoa from the reefs off the Amazon River mouth: checklist, thirteen new species, and notes on their ecology and distribution - Ramalho, Laís V.; Moraes, Fernando C.; Salgado, Leonardo T.; Bastos, Alex C.; Moura, Rodrigo L. (Zootaxa, 2021)
The reef system off the Amazon River mouth extends from Amapá state to Maranhão state along the Brazilian Equatorial Margin, encompassing more than 10,000 km2 of rhodolith beds and high-relief hard structures on the outer shelf and upper slope. This unique hard bottom mosaic is remarkable for being influenced by the turbid and hyposaline plume from the world’s largest river, and also for representing a connectivity corridor between the Caribbean and Brazil. Bryozoans were recently recognized as major reef builders in the Southwestern Atlantic, but their diversity off the Amazon River mouth remained unknown. Here, we report on recent collections obtained from 23 to 120 m depth in Northern Brazil. Sixty-five bryozoan taxa were characterized using scanning electron microscopy, including 57, five and three taxa of Cheilostomatida, Cyclostomatida and Ctenostomatida, respectively. Cribrilaria smitti and three genera (Cranosina, Glabrilaria and Thornelya) are new records for Brazil, and 13 new species are herein described: Antropora cruzeiro n. sp., Cranosina gilbertoi n. sp., Cribrilaria lateralis n. sp., Crisia brasiliensis n. sp., Glabrilaria antoniettae n. sp., Micropora amapaensis n. sp., Parasmittina amazonensis n. sp., Plesiocleidochasma arcuatum n. sp., Poricella bifurcata n. sp., Pourtalesella duoavicularia n. sp., Stephanollona domuspusilla n. sp., Therenia dianae n. sp., and Thornelya atlanticoensis n. sp. Our results highlight the biodiversity significance of the Amazon reefs and the need for more comprehensive sampling to clarify the role of bryozoans in modern turbid-zone reefs and rhodolith beds.